Photosynthetic responses of the desiccation intolerant Sphagnum angustifolium in relation to increasing its desiccation tolerance by exogenous ABA - Marschall, Marianna; Borbély, Péter (Acta Biologica Szegediensis, 2011)
Photosynthetic responses were used to study the effect of exogenous ABA on aspects of desiccation tolerance in a desiccation intolerant bryophyte, Sphagnum angustifolium. CO2-fixation in S. angustifolium and higher plant cells responded similarly to water deficit caused by natural or controlled drying. Ch fluorescence parameters were monitored during slow or rapid desiccation and also upon rehydration. Fv/Fm and & PSII were generally higher in ABA-hardened plants under intensive water stress (below 50% of RWC). ABA-hardening improved recovery of PSII activity upon rehydration, and it resulted in an effective protection of PSII activity against light stress. Activity of PSI was less influenced by exogenous ABA. In the course of slow drying increased thermal energy dissipation was detected. NPQ in S. angustifo-lium – not like in DT bryophytes- saturated with increasing irradiance. During desiccation NPQ did not change until 50% of RWC in ABA-hardened plants, while it increased in control plants. Unlike Atrichum, increased desiccation tolerance was not accompanied by increased NPQ and decreased PS2 efficiency.